Simulation Modeling of the Adaptive System for Hydraulic Drives of a Stalk Forage Separator - Natalia Veselovska; Volodymyr Rutkevych; Serghiy Shargorodskiy; Vitalii Yaropud; Ihor Kupchuk (Журнал інженерних наук)
The article aims to increase the accuracy of the block-portioned stem feed separator, reducing unproductive power losses and dynamic loads in the hydraulic drive of the separator by developing scientific fundamentals based on nonlinear mathematical models and adaptive hydraulic drive systems. The research uses simulation modeling to design an energy-efficient hydraulic drive for a stem feed separator from trench storage. The proposed approach allowed for avoiding significant capital investments to manufacture a prototype. A detailed description of the physical model was carried out. It allowed for checking the results’ reliability and evaluating the rational improvements. As a result, a new design and the corresponding technological scheme of a stem feed separator from trench storage were presented. An approach for simulating transient processes in the hydraulic drive of the separator was also proposed. The experimental design allowed for studying the hydraulic drive in a dynamic mode for different processing loads and various parameters of the adaptive liquid flow separator and the whole system. A close match was found between analytical studies and numerical simulation during the research. This allowed for the recommendation of the obtained dependencies to apply in developing hydraulic drives of stem separators. Moreover, the proposed adaptive hydraulic drive of the stem feed loader allowed for adaptive change in the operation of the cutting unit drive according to the feed. Overall, the possibility of reducing the drive power for the stem feed loader to 5–6 kW was confirmed when using a hydraulic drive system with a mechanism for adapting the working bodies to the operating conditions.